2022
DOI: 10.1021/acs.chemrestox.2c00208
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Identify Electrophiles In Vivo Using Hemoglobin Adducts: Hydroxypropanoic Acid Valine Adduct and Its Possible Precursors

Abstract: Analytical methods and tools for the characterization of the human exposome by untargeted mass spectrometry approaches are advancing rapidly. Adductomics methods have been developed for untargeted screening of short-lived electrophiles, in the form of adducts to proteins or DNA, in vivo. The identification of an adduct and its precursor electrophile in the blood is more complex than that of stable chemicals. The present work aims to illustrate procedures for the identification of an adduct to N-terminal valine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Other Hb adducts have been identified from substances other than glycidol, including ethylene oxide, glyoxal, methyl vinyl ketone, acrylamide, acrylic acid, methyl glyoxal, ethyl vinyl ketone, glycidamide (Carlsson et al., 2019 ), and furfuryl alcohol (Monien et al., 2021 ). Glycidol administration to mice or rats resulted in the formation of a hydroxypropanoic acid valine adduct ( m/z 577) from glycidic acid, a minor metabolite of glycidol (Vryonidis et al., 2022 ). Furthermore, our previous study showed that acrylamide or glucose can affect the formation of diHOPrVal (Shimamura et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other Hb adducts have been identified from substances other than glycidol, including ethylene oxide, glyoxal, methyl vinyl ketone, acrylamide, acrylic acid, methyl glyoxal, ethyl vinyl ketone, glycidamide (Carlsson et al., 2019 ), and furfuryl alcohol (Monien et al., 2021 ). Glycidol administration to mice or rats resulted in the formation of a hydroxypropanoic acid valine adduct ( m/z 577) from glycidic acid, a minor metabolite of glycidol (Vryonidis et al., 2022 ). Furthermore, our previous study showed that acrylamide or glucose can affect the formation of diHOPrVal (Shimamura et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Acrylic acid is used in several industrial applications and can also be produced by the Maillard reaction; it has also been seen to form adducts in hemoglobin . While glycidic acid is not known to be an environmental contaminant, it is believed to be a precursor of a hydroxypropanoic acid adduct observed in human hemoglobin samples …”
Section: Discussionmentioning
confidence: 99%
“…33 While glycidic acid is not known to be an environmental contaminant, it is believed to be a precursor of a hydroxypropanoic acid adduct observed in human hemoglobin samples. 34 The other electrophiles used in this study were chosen due to their documented status as contact allergens, which can induce allergic contact dermatitis (ACD) with repeated exposure. These contact allergens can act as haptens and trigger an immune response when they combine with a carrier protein which the immune system recognizes as "altered self".…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation